FMCW Radar Performance for Atmospheric Measurements - T. Ince (Radioengineering, 2010)
Frequency-modulated continuous-wave radars (FMCW) have been used in the investigation of the atmosphere since the late 1960’s. FMCW radars provide tremendous sensitivity and spatial resolution compared to their pulsed counterparts and are therefore attractive for clear-air remote-sensing applications. However, these systems have some disadvantages and performance limitations that have prevented their widespread use by the atmospheric science community. In this study, system performance of atmospheric FMCW radar is analyzed and some measurement limitations for atmospheric targets are discussed. The effects of Doppler velocities and spectral widths on radar performance, radar’s near-field operation, and parallax errors for two-antenna radar systems are considered. Experimental data collected by the highresolution atmospheric FMCW radar is used to illustrate typical performance qualitatively based on morphological backscattered power information. A post-processing based on single-lag covariance differences between the Bragg and Rayleigh echo is applied to estimate clear-air component from refractive index turbulence and perform quantitative analysis of FMCW radar reflectivity from atmospheric targets.